Factors Leading to Malnutrition in Children Under Five Years in Nyamwamba Division, Kasese Municipality, Kasese District. - Kabugho, Mary Consolata (Kabale University, 2023)
Introduction: The study was carried out to assess the factors leading to malnutrition in children under-five years at Kasese Municipal HCIII, Kasese Municipality, Kasese District. Malnutrition is regarded as the most important risk factor for illness and death globally and it is associated with 52.5% 0f all deaths in young children (Lisanu Mazengia & Andargie Biks, 2018). Methodology: This study used a cross-sectional descriptive research design which used quantitative approaches, researcher-administered questionnaire which was used to determine the factors leading to malnutrition in children under-five years. The study used a probability sampling technique which consisted of a systematic random sampling and 104 respondents were reached. Results: More than half of the under-five children in the study were females (53) and majority were aged 37-59 months (57) and followed by those aged 13-36 months (36) respectively. Half of the children (52) were of birth order 1-2 with a few in the birth order of 3-4 (26) and 5+ order (26) respectively. The number and distribution of under-five children according to the education level of the mother indicates that majority of the mothers had received primary level education (76) and quite a few had never been to school (16). Findings show that 18(104) were wasted and 13 (104) were severely wasted. The highest prevalence of wasting was observed in children aged 24-35 months where 23 (104) and 8 (104) children were wasted and severely wasted respectively. Almost a third, 29 (104) were stunted and 13 (104) severely stunted. Children aged 6-11 month presented highest prevalence of moderate stunting37 (104) while severe stunting was highestl9 (104) in children aged 6-11 months. In conclusion, the study has shown there are some gaps in terms of knowledge towards nutrition. For example only 50 women out of the 104 had the correct knowledge on initiation of breastfeeding after birth. To reduce childhood Under-nutrition in Kasese Municipality which has been on the rise, emphasis should be given in improving the knowledge of mothers on appropriate infant andyoung children feeding. Recommendations l. To reduce childhood Under-nutrition in Kasese Municipality,emphasis should be given in improving the knowledge of mothers on appropriate infant andyoung children feeding. 2. Empowering women in terms of formal education as seen in the current study, education positively affects the correct timing of initiation of complementary feeds. 3. The study recommends exclusive breast feeding and proper supplementary feeding especially among children aged less than three years.